Genome-wide analysis of the CrRLK1L gene family in Puccinellia tenuiflora and functional study of PutFER1 in Arabidopsis underpinning salt tolerance - Li, Gaojian; Peng, Yulin; Liu, Yanshuang; Wu, Zhen; Dai, Shaojun; Qin, Zhi; Sun, Meihong (Frontiers in Plant Science, 2025)
CrRLK1L receptor-like kinases have attracted significant interest in plant biology owing to their pivotal roles in development, stress response, and signal transduction. However, our understanding of their importance in the extreme saline-alkali tolerant mechanisms of the halophyte alkaligrass (Puccinellia tenuiflora) remains limited. In this work, we analyzed the homology and evolutionary relationships of the CrRLK1L gene family across 30 species. Through genome-wide analysis we identified 25 PutCrRLK1L genes, which revealed conserved malectin-like and kinase domain, unique intronless structures, and stress-/hormone-responsive promoter elements. Transcriptomic and RT-qPCR analyses revealed salinity response of nine PutCrRLK1L genes’ expression in roots and leaves. Functional characterization of FER and antioxidant enzyme activities demonstrated that PutFER1-overexpressing Arabidopsis lines exhibited enhanced root growth under salt stress and reduced ROS accumulation compared to wild-type plants. These findings may open new avenues for research into halophyte-specific salt tolerance mechanisms and provide potential candidate genes for improving crop resilience to saline-alkaline soils.